Investigation of Enzymes in the Phthalide Biosynthetic Pathway in Angelica sinensis Using Integrative Metabolite Profiles and Transcriptome Analysis - Feng, Wei-Meng; Liu, Pei; Yan, Hui; Yu, Guang; Zhang, Sen; Jiang, Shu; Shang, Er-Xin; Qian, Da-Wei; Duan, Jin-Ao (Frontiers in Plant Science, 2022)
The roots of Angelica sinensis (Oliv.) Diels are well known for their efficacy in promoting blood circulation. Although many studies have indicated that phthalides are the main chemical components responsible for the pharmacological properties of A. sinensis, the phthalide biosynthetic pathway and enzymes that transform different phthalides are still poorly understood. We identified 108 potential candidate isoforms for phthalide accumulation using transcriptome and metabolite profile analyses. Then, six enzymes, including phospho-2-dehydro-3-deoxyheptonate aldolase 2, shikimate dehydrogenase, primary amine oxidase, polyphenol oxidase, tyrosine decarboxylase, and shikimate O-hydroxycinnamoyl transferase, were identified and proven to be involved in phthalide accumulation by heterologously expressing these proteins in Escherichia coli. We proposed a possible mechanism underlying phthalide transformation and biosynthetic pathways in A. sinensis based on our findings. The results of our study can provide valuable information for understanding the mechanisms underlying phthalide accumulation and transformation and enable further development of quality control during the cultivation of A. sinensis.